2010
DOI: 10.1091/mbc.e10-02-0167
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic Acid Induces Ligand-independent Epidermal Growth Factor Receptor Endocytic Traffic through PDE4 Activation

Abstract: Endocytic traffic can control cell surface versus intracellular distribution of empty/inactive EGFR, an thus its accessibility to external stimuli, through a pathway involving down regulation of PKA activity mediated by PA signaling towards PDE4. This novel control mechanism can trans-modulate EGFR function by heterologous stimuli of PLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(86 citation statements)
references
References 81 publications
5
81
0
Order By: Relevance
“…This could suggest a possible suppressive or regulatory role for PLD2 in signalling. Previous work has shown involvement of PLD in membrane trafficking (Bi et al, 1997) and receptor internalisation (Antonescu et al, 2010;Norambuena et al, 2010). Upon pharmacological inhibition of both PLD1 and PLD2, or inhibition of PLD1 in PLD2KO neutrophils, we have shown an enhanced fMLP-induced ROS response (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…This could suggest a possible suppressive or regulatory role for PLD2 in signalling. Previous work has shown involvement of PLD in membrane trafficking (Bi et al, 1997) and receptor internalisation (Antonescu et al, 2010;Norambuena et al, 2010). Upon pharmacological inhibition of both PLD1 and PLD2, or inhibition of PLD1 in PLD2KO neutrophils, we have shown an enhanced fMLP-induced ROS response (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Our data also suggest that this mechanism is relevant to human physiology, given the significant correlations between adipose tissue lipin 1 expression and lipolytic rates and PKA signaling in obese human subjects. Previous work on PA-mediated regulation of intracellular signaling events, including allosteric activation of mTOR (22) and PDE4 (20,25), linked the activity of PLD and DAG kinase enzymes to controlling this "signaling pool" of PA. An important finding of the present study is that the pool of PA dephosphorylated by lipin 1 that is likely destined for phosphoglycerolipid synthesis can regulate mTOR and PDE4 activity as well. It should be noted that PA was recently found to suppress formation of the mTORC2 complex (26); thus, further work is needed to determine whether mTORC1 is specifically activated by this pool of PA. We also acknowledge that we cannot rule out the possibility that alterations in other lipid species upstream or downstream of PA in these pathways are mediating these signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has linked PA accumulation to increased PDE4 activity in HeLa cells (20), but this "signaling" pool of PA has been thought to be regulated by the actions of phospholipase D (PLD) and other factors. In 3T3-L1 adipocytes, we found that knockdown of lipin 1 elicited a much greater increase in PDE activity than overexpression of PLD (Fig.…”
Section: Role For Pa In Controlling Cyclic Nucleotide Phosphodiesterasementioning
confidence: 99%
“…1B) (Zwang and Yarden 2006). In addition to p38 MAPK-regulated trafficking, internalization of ligand-free EGFR can be induced on activation of protein kinase C (PKC) or inhibition of protein kinase A (PKA) (Beguinot et al 1985;Lin et al 1986;Salazar and Gonzalez 2002;Norambuena et al 2010). In the case of VEGF, the activity of atypical PKC (aPKC) was shown to control vascular endothelial growth factor receptor (VEGFR) internalization and trafficking, thus regulating angiogenesis (Nakayama et al 2013).…”
Section: Stress Factors and Signaling Kinasesmentioning
confidence: 99%